eIF6 affects the occurrence and development of esophageal cancer - Cong-Gai Huang; Xin Zhou; Ran Huang; Hui-Ling Zhang; Chen-Xi Li; Fei Du; Hong Lei; Qiong Dai; Zhi-Hui Yang (Molecular Biology Reports, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Elucidating the thermal degradation of fish oil and algal oil: A comparative study on the evolution of flavor profiles and lipid oxidative pathways - Shuang Cui; Ran Xin; Bo Wang; Tingting Zhang; Xuhui Huang; Lei Qin (Food Research International, 2026)

RETRACTED: Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Steering active hydrogen in PtCu single atom alloy nanowires for efficient nitrate reduction to ammonia - Weimian Zhang; Binwen Zeng; Haoliang Huang; Fan Dang; Xin Liu; Jing Sun; Wei Liao; Mengxiang Han; Chao Song; Run Ran; Kaiyang Xu; Fei Lin; et al. (Chemical Engineering Journal, 2026)

Construction of the CRISPR/Cas12a-digital integrated immunoassay technology for CD44 detection - Songbai Tian; Xin Tang; Saijun Zhang; Yuexin Yao; Ran Bi; Haixia Li; Xiaoming Sun; Zhuo Chen (Analytica Chimica Acta, 2026)

From interfacial stabilization to maintainable operation: fouling-resilient synthetic urine valorization by bipolar membrane electrodialysis - Hao-Ran Yang; Yu Xin; Shu-Jie Hu; Meng-Yue Zhang; Di Wu; Lei Zheng; Lin-Jiang Zhong; Yuan Liu (Water Research, 2026)

Making waves: Harnessing the disinfection byproduct chlorite as an oxidant precursor for micropollutant abatement - Xi Zhang; Yimeng Ma; Mingkai Jia; Wanxin Li; Jiarui Han; Rihui Li; Xin Yang; Ran Yin; Hongqiang Ren (Water Research, 2026)

Assessing contribution of anaerobic methane oxidation and its active methanotrophic communities in landfills - Xin Zhang; Ran Du; Long Han; Wenyong Zhu; Hengyang Chen; Lei Jiang; Ruo He (Waste Management, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Omics-assisted genetic dissection and coordinated improvement of apple flesh color, flavor, and fruit size - Nan Wang; Wenjun Liu; Xuelian Han; Zhiqiang Li; Xin Jing; Zongying Zhang; Hongcheng Fang; Shuhui Zhang; Haifeng Xu; Qi Zou; Lei Yu; Tongyao Xu; et al. (Molecular Plant, 2026)

Retraction notice to “Metastable conformational regulation in heat-induced gluten aggregation: multiscale experiments and molecular dynamics reveal distinct roles of HMW-GS at the Glu-B1 locus” [Food Hydrocolloids 179 (2026) 112791] - Bo Wang; Ping-ping Zhang; Rong-ran Zhang; Tian Lv; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Xin-long Dai; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

TRIF signaling is essential for the activation of dendritic cells during porcine rotavirus infection - Yu Sun; Tianming Niu; Ran Zhang; Danni Li; Mingyang Cheng; Chenxi Jiang; Yiran Shao; Hongyuan Wang; Ziqun Guo; Wentao Yang; Xin Cao; Chunfeng Wang; et al. (Veterinary Microbiology, 2026)

Peak greening at moderate shrinking intensity across Chinese counties - Ran Chen; Wenxiao Jia; Kai Wang; Xinyuan Zhang; Jiaxuan Xin; Wenjian Li; Zhijun Zhang; Junling He (Journal of Environmental Management, 2026)

A fast estimation method for pulsar signal period based on point cloudization of photon arrival times - Shuo Zhang; Xin Ma; Wenjia Zhang; Tianhao Xie; Shanchuan Ran; Peiling Cui; Xiaolin Ning (Advances in Space Research, 2026)

Simulation-Based Maritime Scheduling Optimization for Bidirectional Ship Flow in Multi-Chamber Lock Systems: Incorporating Chamber Operations for Efficient Management - Nini Zhang; Xin Li; Wen Xie; Sudong Xu; Weikai Tan; Cheng Cheng; Ran Yan (Journal of Marine Science and Engineering, 2026)
This paper addresses the bidirectional multi-chamber lock scheduling problem by formulating a multi-objective mixed-integer linear programming (MILP) model that simultaneously minimizes average ship waiting time and maximizes chamber utilization. A tailored adaptive large neighborhood search (ALNS) algorithm is developed specifically based on the principle of the destruction and reconstruction of solutions. The algorithm efficacy is validated using the real-word data from Huai’an Lock of the Subei canal. The scheduling rules and parameters are defined from practical operation records. Simulation results demonstrate that the ALNS-based optimization significantly improves lock performance with average chamber utilization increasing by 12.98% and waiting time decreasing by 44.40%. Sensitivity analyses on objective weights further confirm the robustness of the proposed method. Benchmark comparisons with a greedy heuristic, genetic algorithm (GA), and particle swarm optimization (PSO) highlight the effectiveness and computational efficiency of ALNS. This study further explores a threshold-based directional control strategy, showing that relaxing strict alternating-direction rules under asymmetric traffic demand can improve efficiency. The findings provide practical insights for lock scheduling, offering decision support for lock authorities in designing adaptive scheduling and directional control policies.

Ion-specific multiscale regulation of gelatinization and retrogradation in normal and waxy wheat starches: Cooperative roles of valence, hydration, and molecular chain architecture - Tian Lv; Xin-rong Lv; Shu-ning Yuan; Yu Hu; Rong-ran Zhang; Yue Zhang; Chuan Zhong; Pei Wang; Qin Zhou; Dong Jiang; Hao Jiang; Tao Yang (Food Hydrocolloids, 2026)

Integrated metabolomic and transcriptomic analyses unravel the function of quercetin in enhancing grape resistance to anthracnose - Meng-Fei Li; Ming-Yi Wang; Fu-Lai Han; Zhe Zhang; Ya-Lin Liu; Meng-Ran Li; Yu-Fei Li; Jie Yang; Xin Liu; Guang-Chao Liu (Postharvest Biology and Technology, 2026)

Collagen films enhanced with bovine hide-tannic acid carbon dots: A traditional tanning-inspired strategy for crispy fried chicken preservation - Linjing He; Ruimin Ran; Xin Guo; Wenli Shi; Zhijie Zhang; Guoying Li (Food Hydrocolloids, 2026)

Porous MXene nanoplatform with ultrahigh drug loading for synergistic photothermal/photodynamic therapy and drug resistance reversal in osteosarcoma - Zhen Song; Ran-Ran Zhang; Zi-Chao Yan; Jie Wang; Youchang Liu; Chang-Qing Jiang; Meng Qiu; Bing-Xin Zheng; Bin Yue (Chemical Engineering Journal, 2026)

Overexpression of PtrPYL11 enhance drought tolerance in Populus: evidence from genome-wide identification and comparative transcriptome profiling - Shuang-Lian Deng; Shu-Ying Wei; Rui-Quan Wang; Yuan Zhang; Hao Li; Xing-Yu Liu; Xin-Ran Yu; Guan-Ru Ren; Ting Wang; Fang He (Plant Cell Reports, 2026)

Emergence of a novel porcine reproductive and respiratory syndrome virus strain inducing biphasic temperature fluctuations in Tianjin, northern China - Jia Wang; Yi-Han Lu; Bo-Han; Hai-Tao Yang; Xin-lei Li; Wen Sun; Shi-Qin Zhang; Zhuo-Ran Miao; Xue-Jiao Cheng; Chun-Xue You; Ying-Feng Sun (Research in Veterinary Science, 2026)

Uncovering pH-driven metastable transitions and thermal aggregation of HMW-GSs via all-atom molecular dynamics simulations - Tao Yang; Rong-ran Zhang; Xin-rong Lv; Tian Lv; Bo Wang; Yue Zhang; Pei Wang; Qin Zhou; Dong Jiang; Zhe Liu; Hao Jiang (Food Hydrocolloids, 2026)

Distinct Role of Specialized Cutaneous Schwann Cell Network in Acute and Chronic Pain Sensation - Shan-Xin Zhang; Jing Yang; Yao Lou; Song-Cheng Xu; Ran Guo; Zhen-Zhong Xu (Neuroscience Bulletin, 2026)

Unveiling the molecular mechanisms of dihydromyricetin regulating the biosynthesis of three key secondary metabolites in Monascus purpureus HBSD08 through integrated transcriptomic and metabolomic analyses - Ran Fang; Yingying Wang; Jie Qiao; Di Wu; Qianyu Gao; Chunzheng Han; Penghui Sun; Wanting Wang; Xin Zeng; Bingyue Xin; Biao Zhang; Deyin Zhao; et al. (Food Bioscience, 2026)

Advanced functionalization strategies of chitin and chitosan toward sustainable nanocomposites - Shuang-Lin Zou; Xin-Ran Liu; Jia-Hui Zhang; Ying-Chun Xu; Qiang Wang; Ling-Ping Xiao; Run-Cang Sun (Carbohydrate Polymers, 2026)

Sex differences in locomotor recovery across mating contexts in Drosophila melanogaster - Rui Han; Jun Zhang; Xin-Hui Chen; Jing-Wen Duo; Yi-Yi Li; Yi-Ran Chen; Si-Tong Chen; Lin-Xiang Liu; Xiang-Haoran Lin (Behavioural Processes, 2026)

Study on the Applicability of Intelligent Recognition Algorithms to Different Types of Subgrade Defects - Yu-xuan Han; Yan-li Qi; Yi Zhang; Yi-guo Xue; Jiang Zhao; Fan-meng Kong; Sheng-yong Dong; Gang Li; Xin-shun Li; Ao-xiong Shu; Hao-ran Zhu (Applied Geophysics, 2026)

Rhein Prevents APAP-induced drug-induced Liver Injury by Upregulating Nrf2 and Inhibiting APAP-activating Enzymes - Mingda Liu; Jin Dai; Liangding Dou; Zifeng Deng; Junxian Liu; Xin Hou; Jinwen Zhang; YongChao Huang; Zhi Huang; Dai Wang; Dongbei Guo; Ran An; et al. (Cell Biochemistry and Biophysics, 2026)

Curcumin-mediated photodynamic action disturbs TOM70-depedent MIC60 import to damage mitonchondria against breast cancer - Xiang-Yi Zhao; Min Yan; Liang Zheng; Chang-Long Gou; Qi Huang; Liu-Gen Li; Xin-Ran Yu; Jing-Yu Lu; Cui Hu; Si-Han Zhang; Cunqing Kong; Fan Leng; et al. (Journal of Photochemistry and Photobiology B: Biology, 2026)

Role of Ni-Co bimetals in CaCr2O4 catalysts for dry reforming of methane: Promotion in coke resistance - Jie Gao; Hangjia Zhang; Jingyu Ran; Chuan Ma; Xin Huang; Yunlin Shao; Huayu Qiu; Zhiliang Ou; Lei Tang (Fuel, 2026)

Photothermal-brick for on-site zero liquid discharge treatment of high-salinity wastewater - Xuxiao Luo; Yingru Li; Xin Yang; Daolin Quan; Yulin Ran; Youshuai Lan; Jianfeng Zhang; Yahui Yang; Jinyu Liu; Zihao Luo; Zhuxin Jiang; Miaowei Zhang; et al. (Environmental Research, 2026)

High-Fidelity Morphological and Mineralogical Reconstruction of Chang’E-5 Lunar Regolith Grains - Quan Zheng; Ziwei Tian; Songzheng Yu; Ronghua Pang; Guang Zhang; Guanghui Liu; Yiwei Liu; Yang Li; Xin Liu; Shijing He; Ran Niu; Peng Zhang (Computers and Geotechnics, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

DLP 3D printing of high-performance thermosetting polymers with photothermal dual-curing resin containing reversible covalent bonds - Lingyu Zhao; Pengyi Wang; Xiaojuan Zhao; Xin Yang; Ying Zhang; Bing Cheng; Wei Huang; Ran Yu (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

CD33 Isoform Splicing Dysregulation: A Molecular Determinant of Microglial Dysfunction in Alzheimer’s Disease Pathology - Xiao-Yan Li; Yu Zhang; Zhao Ran; Jia-Xin Luo; Xiao-Qin Yu; Mei-Hong Lu (Molecular Neurobiology, 2026)

Nicotinamide delays browning in fresh-cut apples through reducing Chlorogenic acid and inhibiting PPO activity - Chen Wang; Lu-Ping Dai; Xin-Ran Bai; Song Zhang; Pei-Qiang Dai; Bao-Long Zhao; Feng-Yun Zhao; Da-Gang Hu (Food Chemistry, 2025)

Machine learning-assisted identification of core flavor compounds and prediction of core microorganisms in fermentation grains and pit mud during the fermentation process of strong-flavor Baijiu - Jiang Xie; Jiaxin Hong; Chunsheng Zhang; Xin Yuan; Zhigang Zhao; Dongrui Zhao; Shimin Wang; Baoguo Sun; Ran Ao; Jinyuan Sun; Yuling Sun; Mingquan Huang; et al. (Food Chemistry, 2025)

Ultra-tough and autonomous self-healing polyurethane based on dynamic pyrrolidine-urea bonds and their coordination complex - Lingyu Zhao; Pengyi Wang; Pingxia Zhang; Xiaojuan Zhao; Xin Yang; Ying Zhang; Bing Cheng; Wei Huang; Ran Yu (Chemical Engineering Journal, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Aridity Drives the Response of Soil Organic Carbon and Inorganic Carbon to Drought in Cropland - Shou‐Wei Han; Qing Luo; Zhi‐Heng Qin; Wen‐Sheng Liu; Hao‐Ran Li; Rattan Lal; Yash Pal Dang; Pete Smith; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2025)
In the face of a warming climate and increasing extreme weather events, understanding the trade‐offs between soil organic carbon (SOC) and inorganic carbon (SIC) under drought is critical for accurately assessing global soil carbon (C) sequestration. However, previous research has predominantly focused on SOC, despite emerging evidence indicating that SIC is highly sensitive to soil moisture dynamics. Using global soil profile C measurements, this study compares the relative ratio of SOC and SIC to soil total carbon (STC) in cropland to assess the impact of climatic drought on soil C pools. The research findings revealed that STC stocks averaged 8.0, 16.7, and 21.6 kg C m −2 at soil depths of 0–30 cm, 30–100 cm, and 100–200 cm, respectively. The STC in the deep soil depths (100–200 cm) responded linearly to the drought gradient, whereas STC in the surface layer showed a nonlinear response. It is notable that the ratio of SIC to STC increased along the drought gradient. Irrigation, a key drought mitigation strategy, increased the ratio of SIC in dry sub‐humid regions but reduced it elsewhere. These findings highlight the importance of incorporating SIC into climate change mitigation strategies, especially in the context of intensifying drought conditions.

In-situ formation of green rust during Fe(II) coagulation: Dual reductive and adsorptive pathways for dyeing wastewater treatment - Xian Zhao; Jia-Yi Wang; Yu-Qian Wang; Chen-Hao Cui; Xin Yan; Wei Dai; An-Ran Zhang; Zhen-Ying Zhang; Ding-Ding Tang; Yan Zhou; Qiong Qin; Ji-Wei Pang; et al. (Water Research, 2025)

A copper-based single-atom material effectively controls plant diseases with nearly zero soil residue and low phytotoxicity - Rui Huang; Yong Yan; Yafei Jiang; Chunyan Gu; Zhentao Ma; Lifang Xue; Yao Ma; Xingen Lin; Juan Zhang; Ran Shi; Yiwen Wang; Linjing Liu; et al. (Science Bulletin, 2025)

Unraveling the surface and interface reaction mechanisms of CO2 hydrogenation to methanol over Ga-modified Cu-based catalysts: Insights from DFT calculations - Jie Gao; Hangjia Zhang; Jingyu Ran; Guohua Sang; Zhiliang Ou; Lei Tang; Huayu Qiu; Yunlin Shao; Chuan Ma; Xin Huang (Journal of Environmental Chemical Engineering, 2025)

A ratiometric fluorescent probe for sensitive detection of benzoyl peroxide and hypochlorite in food - Shun-Qiang Cui; Xin-Yi Liang; Zhi-Qiang Cai; Hou-Qun Yuan; Qiu-Yu Zhang; Yi-Fan Xia; A.K.I.M.A.N.A. Sandra; Ling-Yi Guo; Ran Wang; Shi-Yu Zhao; Yan-Xia Li; Guang-Ming Bao (Food Chemistry, 2025)

Multifunctional bending sensor based on PLA hierarchical porosity: smart wearable device with wide range response, self-powered capability and biodegradable - Jun Hou; Danqing Zhang; Qi Ran; Geran Yin; Manlin Wang; Wenhao Yang; Hua Wang; Yi Xiong; Xin Liu; Heng Pan; Liangjun Xia; Weilin Xu (Chemical Engineering Journal, 2025)

Effect of primate protection on threatened and endemic vertebrates, plants, ecosystem services, and future climate refugia - Yin Yang; Chen Li; Yi‐Hao Fang; Guo‐Peng Ren; Zhi‐Pang Huang; Yan‐Peng Li; Liang‐Wei Cui; Meng‐Ran Chu‐yuan; Colin A. Chapmman; Cyril C. Grueter; Jian Zhou; Wen‐Bo Yan; et al. (Conservation Biology, 2025)
Primates, 69% of which are threatened with extinction, are the third most specious order of mammals. We used primates as model taxa to examine the umbrella effects of primates on ecosystem services and the protection of other vertebrates and seed plants in Yunnan Province, China. We identified areas of conservation priority for 16 primate species and determined which other threatened and endemic terrestrial vertebrates and seed plants would be protected through a program targeting primate conservation. Areas of high primate species richness were spatially correlated with the distribution of 601 species of threatened and endemic vertebrates and 4010 seed plants. Primate species richness was positively correlated with carbon sequestration and enhanced water and soil conservation and coincided with future areas of climate refugia. If 30% of Yunnan's land area were designated as primate conservation priority areas, then 52.3% of the province's average annual carbon sequestration, 51.7% of its water conservation, 54.1% of its soil retention, and 30‐33% of its climate‐stable areas would be protected. Protecting primates as umbrella taxa uniquely contributes to maintaining biodiversity and ecosystem services that promote ecosystem stability. Although we focused on a single mammalian order in a single region, our approach for umbrella taxa evaluation has broad applicability and can help achieve multiple conservation targets of the Kunming–Montreal Global Biodiversity Framework.

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

Effect of H2 content on the evolution process of CH4/H2 explosion pressure and flame structure - Shanshan Liu; Dongxu Huang; Yong Pan; Yingquan Qi; Lingxiu Yan; Zhenhua Wang; Xin Zhang; Ran Ye; Juncheng Jiang (Process Safety and Environmental Protection, 2025)

Asymmetric C2-functionalization of indoles via visible-light-promoted three-component reaction - Han-Peng Pan; Xiao-Ying Hu; Jun-Hui Luo; Zhao-Jie Fu; Xin-Yi Yao; Meng-Yan Ran; Fang-Xin Wang; Xiang-Zhi Zhang (Molecular Diversity, 2025)

“Using waste straw to prevent pollution”: Enabling closed-loop design of chrome-free tanning agent with tanning-masking dual effect - Huaqing Liu; Taotao Qiang; Ran Zhang; Ruilong Li; Xin Sun; Sijie Yu; Chao Wu; Longfang Ren (Waste Management, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Palmitic acid triggers rhizosphere acidification to facilitate microbial nitrogen fixation: A perspective for phytoremediation of desertification alpine grassland via artificial root exudation mimicking - Fei Yan; Qian Huang; Dongming Chen; Xin Zheng; Rui Yin; Kangqi Zhang; Yan Lu; Yanfu Bai; Feida Sun; Jiqiong Zhou; Zhouwen Ma; Geng Sun; et al. (Journal of Environmental Management, 2025)

Modeling the elongation of commingled BTEX and chlorinated ethene plumes undergoing biodegradation with a multi-level substrate interaction module - Moye Luo; Xiaodong Zhang; Shaohua Cao; Qiang Chen; Xin Zhu; Chenghua Xu; Dandan Yu; Manjun Zhan; Ran Yu; Tao Long (Journal of Hazardous Materials, 2025)

A green-solvent processed multifunctional bamboo composite with high strength, robust fire retardancy, and dimensional stability - Xiangyu Ren; Huijun Zhang; Weibing Xue; Tongda Liu; Rong Liu; Xin Ran; Ping Wang; Wei Gao; Yanmei Li; Guanben Du; Long Yang (Chemical Engineering Journal, 2025)

Monocot-like leaf structure and trichome-water relations in early growth stages of the C3 plant sand rice (Agriophyllum squarrosum) - Ruilan Ran; Xiaofeng Li; Jiwei Zhang; Jiecai Zhao; Xin Zhao; Xiaoyun Cui; Guoxiong Chen; Pengshan Zhao (Plant Science, 2025)

Regional differentiation of the pollution reduction effect of accountability audit of natural resource under the perspective of spatial mismatch in land supply: evidence from China - Xin Zhang; Qiying Ran; Yang Xu; Yuan Jin; Wenfeng Ge (Journal of Environmental Management, 2025)

Identifying the flows and stocks of additives in polyvinyl chloride plastics for balancing environmental and economic impacts - Kai Zhao; Zhenye Zhang; Yijun Li; Hang Fu; Xiting Peng; Ran Tao; Zhiyuan Li; Weigu Wen; Xin Xie; Shanying Hu (Resources, Conservation and Recycling, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

Simultaneous extraction of flavonoids and saponins from functional food via basic deep eutectic solvent-assisted mechanochemical extraction - Yi-Wen Wu; Jie Zhang; Xin-Ran Ma; Jun Cao (Food Chemistry, 2025)

Flexible surface acoustic wave technology for enhancing transdermal drug delivery - Jikai Zhang; Duygu Bahar; Hui Ling Ong; Peter Arnold; Meng Zhang; Yunhong Jiang; Ran Tao; Luke Haworth; Xin Yang; Chelsea Brain; Mohammad Rahmati; Hamdi Torun; et al. (Drug Delivery and Translational Research, 2025)
Transdermal drug delivery provides therapeutic benefits over enteric or injection delivery because its transdermal routes provide more consistent concentrations of drug and avoid issues of drugs affecting kidneys and liver functions. Many technologies have been evaluated to enhance drug delivery through the relatively impervious epidermal layer of the skin. However, precise delivery of large hydrophilic molecules is still a great challenge even though microneedles or other energized (such as electrical, thermal, or ultrasonic) patches have been used, which are often difficult to be integrated into small wearable devices. This study developed a flexible surface acoustic wave (SAW) patch platform to facilitate transdermal delivery of macromolecules with fluorescein isothiocyanates up to 2000 kDa. Two surrogates of human skin were used to evaluate SAW based energized devices, i.e., delivering dextran through agarose gels and across stratum corneum of pig skin into the epidermis. Results showed that the 2000 kDa fluorescent molecules have been delivered up to 1.1 mm in agarose gel, and the fluorescent molecules from 4 to 2000 kDa have been delivered up to 100 µm and 25 µm in porcine skin tissue, respectively. Mechanical agitation, localised streaming, and acousto-thermal effect generated on the skin surface were identified as the main mechanisms for promoting drug transdermal transportation, although micro/nanoscale acoustic cavitation induced by SAWs could also have its contribution. SAW enhanced transdermal drug delivery is dependent on the combined effects of wave frequency and intensity, duration of applied acoustic waves, temperature, and drug molecules molecular weights. Graphical Abstract Graphical Abstract: Flexible surface acoustic wave technology for enhancing transdermal drug delivery

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

Development of multi-functional collagen films for maintaining and visually monitoring shrimp freshness - Ruimin Ran; YeQing He; Xiaoxia Zhang; Xingling Zeng; Xin Guo; Xiaoyun Luo; Guoying Li (Food Hydrocolloids, 2025)

MMCPT: A high-efficiency multiplexed metabolomics approach for rapid differential metabolite discovery using enzymatically cleavable chemoselective probe and TMT labeling - Lu Ye; Xue-Man Dong; Pei-Ran Miao; Yu-Xin Xu; Pu Wu; Ji-Lei Zhao; Hua-Min Zhang; Bing-Jun Zhou; Hui Zhang; Yuanyuan Lin; Jian-Liang Zhou (Chemical Engineering Journal, 2025)

Functional characterization and site-directed mutagenesis of a novel UDP-glycosyltransferase from Panax japonicus var. major - Lu Mou; Yang Zhang; Yu-Xin Zhuang; Rui-Fang Ren; Ran Xu; Ling Yang; Shao-Peng Zhang; Deng-Xiang Du (Planta, 2025)

Enhanced catalytic decomposition of methyl formate to carbon monoxide and methanol using palladium/activated carbon catalyst: Mechanistic insights and catalyst design considerations - Wei Shen; Xin Zhang; Yuanyuan Huang; Liyuan Xu; Ran Wang; Wenxing Yang; Pengbin Pan; Yuan-Gen Yao (Fuel, 2025)

Effects of decapitation on yield-related traits of total node number per plant in soybean - Ran Fang; Yichun Wu; Xin Huang; Zhihong Hou; Jialin Zhang; Lingshuang Wang; Yanan Wang; Yaru Li; Liyu Chen; Hui Yang; Lin Yue; Haiping Du; et al. (Field Crops Research, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Enhanced priming effect in agricultural soils driven by high-quality exogenous organic carbon additions: A meta-analysis - Yuyao Zhang; Hongyu Hu; Yiguo Ran; Ping Huang; Yunlong Cai; Lin Chen; Congzhi Zhang; Xin Gao; Donghao Ma; Jiabao Zhang (Science of The Total Environment, 2025)

Synergistic structural engineering and electronic modulation enhance upconversion emission and charge separation in LiYF4: Yb3+, Tm3+@LiYF4:Nd3+@LixTi1-xO2 core-shell nanostructure for efficient near-infrared photocatalysis - Yuxiang Xin; Jianru Wang; Ran Jia; Chaochao Dun; Zhuolei Zhang (Chemical Engineering Journal, 2025)

A stab-/solvent-resistant HAG/silicone armor for durably stretchable electroluminescent device - Jun-Yue Li; Xin-Kai Qian; Qi-Ye Wang; Hong-Chao Sun; Xiu-Juan Li; Zhen-Yu Zhang; Chao-Ran Huang; Rui Guo; Fei Xiu; Ju-Qing Liu (Chemical Engineering Journal, 2025)

Ultra-elastic conductive silicone rubber composite foams for durable piezoresistive sensors via direct ink writing three-dimensional printing - Zehua Zhao; Jiawen Ji; Ying Zhang; Jiwei Liu; Ran Yu; Xin Yang; Xiaojuan Zhao; Wei Huang; Wei Zhao (Chemical Engineering Journal, 2025)

Multiphysics simulation and optimization of the in-situ beneficiation process of ilmenite minerals from lunar regolith - Peng Zhang; Xin Liu; Guanghui Liu; Wei Dai; Hanzhe Yang; Haibo Zheng; Zhi Wang; Ran Niu; Yifan Bai; Yang Zhang; Chengbao Liu; Ge Yang; et al. (Science China Earth Sciences, 2025)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Reconstruction of large-scale anisotropic 3D digital rocks from 2D shale images using generative adversarial network - Peng Chi; Jianmeng Sun; Ran Zhang; Xin Luo; Weichao Yan (Marine and Petroleum Geology, 2024)

Comprehensive analysis of biotransformation pathways and products of chloramphenicol by Raoultella Ornithinolytica CT3: Pathway elucidation and toxicity assessment - Xueping Jiang; Hao Li; Jia Kong; Yuqi li; Xiangdong Xin; Jielin Zhou; Ran Zhang; Kwang Sik Lee; Byung Rae Jin; Zhongzheng Gui (Journal of Hazardous Materials, 2024)

Effects of plastic aging on biodegradation of polystyrene by Tenebrio molitor larvae: Insights into gut microbiome and bacterial metabolism - Meng-Qi Ding; Jie Ding; Shan-Shan Yang; Xin-Ran Ren; Shao-Nan Shi; Lu-Yan Zhang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu (Science of The Total Environment, 2024)

An “intelligent-sensing and targeted release” antimicrobial pickering emulsion for banana preservation - Ruimin Ran; Xiaoxia Zhang; Xin Guo; Changkai Yang; Fang Zhang; Guoying Li (Food Hydrocolloids, 2024)

Greenhouse gas emissions and mitigation potential of crop production in Northeast China - Jin-Sai Chen; Hao-Ran Li; Yu-Gang Tian; Ping-Ping Deng; Olatunde Pelumi Oladele; Wei Bai; Yash Pal Dang; Xin Zhao; Hai-Lin Zhang (European Journal of Agronomy, 2024)

Soil organic phosphorus is mainly hydrolyzed via phosphatases from ectomycorrhiza-associated bacteria rather than ectomycorrhizal fungi - Jing Yuan; Rui Yan; Xueqiong Zhang; Kai Su; Hui Liu; Xin Wei; Ran Wang; Lanlan Huang; Nianwu Tang; Shanping Wan; Wei Liu; Hans Lambers; et al. (Plant and Soil, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Gigantic gastropods from the Middle Triassic Qingyan biota of Guizhou - Xin Sun; Li Tian; Chuan-Yuan Liu; Xiao He; Dao-Liang Chu; Xue Miao; Shi-Yan Zhang; Yi-Ran Cao; Pei-Shan Li; Jin-Nan Tong; Hai-Jun Song (Palaeoworld, 2024)

Characteristics of corn starch/polyvinyl alcohol composite film with improved flexibility and UV shielding ability by novel approach combining chemical cross-linking and physical blending - Hao-Nan Wei; Xin-Yue Liu; Chen-Chen Wang; Ran Feng; Bao Zhang (Food Chemistry, 2024)

Visual environment in schools and student depressive symptoms: Insights from a prospective study across multiple cities in eastern China - Xiyan Zhang; Jiawen Tang; Yan Wang; Wenyi Yang; Xin Wang; Ran Zhang; Jie Yang; Wei Lu; Fei Wang (Environmental Research, 2024)

Robust fatigue markers obtained from muscle synergy analysis - Chen Zhang; Zi-jian Zhou; Lu-yi Wang; Ling-hua Ran; Hui-min Hu; Xin Zhang; Hong-qi Xu; Ji-peng Shi (Experimental Brain Research, 2024)

An approach for estimating microbial growth and chlorinated ethenes biotransformation in groundwater based on discrete observations - Moye Luo; Shaohua Cao; Chenghua Xu; Xiaodong Zhang; Xin Zhu; Manjun Zhan; Dandan Yu; Tao Long; Ran Yu (Environmental Pollution, 2024)

Probabilistic stability analysis of a layered slope considering multi-factors in spatially variable soils - Wengang Zhang; Bo Ran; Xin Gu; Guanhua Sun; Yulin Zou (Natural Hazards, 2024)

Studies on 1-deoxynojirimycin biosynthesis in mulberry ( Morus alba L.) seeds through comparative transcriptomics - Xiangdong Xin; Xueping Jiang; Attaribo Thomas; Baoxin Niu; Minqi Zhang; Xueming Xu; Ran Zhang; Hao Li; Zhongzheng Gui (Natural Product Research, 2024)

Sludge biolysis pretreatment to reduce antibiotic resistance genes (ARGs): Insight into the relationship between potential ARGs hosts and BALOs' preferred prey - Siyuan Zhang; Tingting Cui; Xiaowen Liu; Manjun Zhan; Xin Song; Yi Xu; Ran Yu (Water Research, 2024)

Geochronology and Sr-Nd-Pb-Hf-O isotopes of Neoproterozoic orthogneisses in the Jiamusi Block, NE China: Implications for tectonic origin and secular crustal evolution - Xin Ding; Hao Yang; Zheng Ji; Yan-Long Zhang; Hao-Ran Wu; Yu Dong; Guan-Ying Yu; Wen-Chun Ge (Precambrian Research, 2024)

Involvement of CgHSFB1 in the regulation of self-incompatibility in ‘Shatian’ pummelo - Chenchen Liu; Xin Zheng; Jianbing Hu; Qiang Xu; Hao Wen; Zhezhong Zhang; Ran Liu; Xiangling Chen; Zongzhou Xie; Junli Ye; Xiuxin Deng; Lijun Chai (Plant Molecular Biology, 2024)

The protective effect and mechanism of piperazine ferulate in rats with 5/6 nephrectomy-caused chronic kidney disease - Xiu-Meng Zhang; Xin-Ran Min; Dan Li; Bo Li; Yi-Xin rui; Hong-Xiao Xie; Rong Liu; Nan Zeng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

The fabrication of Mn single atoms/clusters on Al2O3 for enhanced catalytic NO oxidation - Xiao-Ke Hou; Hui-Xin Zhang; Yi-Bo Wang; Jin-Ping Zhang; Xin Gao; Lei Chen; Chao Li; Hong-Mei Jing; Chi He; Qiang Lu; Chun-Ran Chang (Fuel, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Bioinspired 3D printed elastomer-hydrogel hybrid with robust interfacial bonding for flexible ionotronics - Feng Tian; Ran Yu; Xiaobiao Zuo; Manwen Zhang; Lingyu Zhao; Xiaojuan Zhao; Xin Yang; Ying Zhang; Wei Huang (Chemical Engineering Journal, 2024)

Cenozoic Indo-Pacific warm pool controlled by both atmospheric CO2 and paleogeography - Ran Zhang; Zhonghui Liu; Dabang Jiang; Yongqiang Yu; Zhongshi Zhang; Yibo Yang; Ning Tan; Dong Si; Qiang Zhang; Xin Zhou (Science Bulletin, 2024)

Influence of the community assemblage on sulfur distributions in the South China sea - Hao-Quan Zhang; Juan Yu; Jing-Guang Lai; Gui-Peng Yang; Long-Fei Liu; Yu Jiang; Xin-Ran Song; Yong-Qiao Chen; Hou-Jin Zhou; Qi Zhang (Marine Environmental Research, 2024)

Rhythmic mild photothermal therapy enhancing anti-PD-L1 response for oral squamous cell carcinoma immunotherapy - Tao Liu; Shilin Guo; Dongyao Zhang; Diya Xie; Xinyu Zhang; Lin Chen; Yanyi Wang; Huihui Zou; Linzhong Yang; Meng Zhou; Xin Tong; Jianchuan Ran; et al. (Chemical Engineering Journal, 2024)

Spatially resolved glacial meltwater retainment in glacial lakes exerts increasing impacts in High Mountain Asia - Xin Wang; Weijie Ran; Junfeng Wei; Yongsheng Yin; Shiyin Liu; Tobias Bolch; Yong Zhang; Xijing Xue; Yongjian Ding; Qiao Liu; Yanlin Zhang; Lufang He (Journal of Hydrology, 2024)

Film-Depth-Dependent Charge Mobilities in Organic Semiconductor Films - Qingyu Wang; Peng Wei; Zongze Qin; Yixin Ran; Xin Wang; Peng Zhang; Guanghao Lu (Chemical Engineering Journal, 2024)

Increasing lateral transport of soil and carbon on the Tibetan Plateau - Yanzhang Huang; Zhongbao Xin; Guangyao Gao; Xixi Lu; Lishan Ran; Yafeng Wang; Zhiqiang Zhang (CATENA, 2024)

The spatial transcriptomic landscape of human gingiva in health and periodontitis - Zongshan Shen; Ran Zhang; Yunjia Huang; Jiayao Chen; Mengjun Yu; Chunhua Li; Yong Zhang; Lingling Chen; Xin Huang; Jichen Yang; Zhengmei Lin; Songlin Wang; et al. (Science China Life Sciences, 2024)

KDM4B down-regulation facilitated breast cancer cell stemness via PHGDH upregulation in H3K36me3-dependent manner - Xin-Yu Wang; Hong-Ming Li; Ran Xia; Xiang Li; Xing Zhang; Tong-Zhao Jin; Hong-Sheng Zhang (Molecular and Cellular Biochemistry, 2024)

On the contributions of refined thermal expansion model to nonlinear variations in different GNSS height time series products - Ran Lu; Zhao Li; Qusen Chen; Xin Ding; Kaichun Yang; Mingyuan Zhang; Yang Lu; Wenlan Fan; Hua Chen; Weiping Jiang (GPS Solutions, 2024)

Modulation of pea protein isolate nanoparticles by interaction with OSA-corn starch: Enhancing the stability of the constructed Pickering emulsions - Xin-Yue Liu; Ting-Shi He; Chen-Chen Wang; Bao-Cai Xu; Ran Feng; Bao Zhang; Han Tao (Food Chemistry, 2024)

Effects of nanoplastics exposure on ingestion, life history traits, and dimethyl sulfide production in rotifer Brachionus plicatilis - Juan Yu; Su Wang; Hao-Quan Zhang; Xin-Ran Song; Long-Fei Liu; Yu Jiang; Rong Chen; Qi Zhang; Yong-Qiao Chen; Hou-Jin Zhou; Gui-Peng Yang (Environmental Pollution, 2024)

Tumor microenvironment-activated hollow vanadium-based nanoplatform for precise therapy of lung cancer through synergistically reversing cisplatin resistance - Lang Ran; Jianmin Xiao; Weijie Zhang; Miaomiao Wang; Huan Xin; Huimin Li; Hong Hao; Maoyang Wang; Xiaofei Wang; Geng Tian; Guilong Zhang (Chemical Engineering Journal, 2024)

Revisiting the physical processes controlling the tropical atmospheric circulation changes during the Mid-Piacenzian Warm Period - Ke Zhang; Yong Sun; Zhongshi Zhang; Christian Stepanek; Ran Feng; Daniel Hill; Gerrit Lohmann; Aisling Dolan; Alan Haywood; Ayako Abe-Ouchi; Bette Otto-Bliesner; Camille Contoux; et al. (Quaternary International, 2024)

Conversion mechanism for solving the end-stop problem of hydraulic power take-off system for wave energy - Dahai Zhang; Chenglong Li; Ran Bi; Xin Huang; Zhiwei Sun; Tianlong Lan; Yuankui Wang; Ting Huang; Peng Qian (Ocean Engineering, 2024)

Experimental and computational insight into the role of cobalt and phosphorus in boosting Volmer and Heyrovsky steps of Ni in alkaline hydrogen evolution reaction - Wei Xu; Xian-Qing Tang; Zhen Zhang; Yi-Ran Wang; Jian-Long Luo; Isack Bulugu; Wen-Jie Yin; Xin Tang; Yu Shen (Fuel, 2024)

Revisiting dispersion and reactivity of active sites via a restricted random distribution model over supported vanadia catalysts for NO reduction - Jingyu Xue; Yang Zhang; Wenshuo Hu; Yanrong Chen; Zhongqing Yang; Jingyu Ran; Xinbao Li; Xin Tu; Xuesen Du (Fuel, 2024)

Environmental surveillance in Jinan city of East China (2014–2022) reveals improved air quality but remained health risks attributable to PM2.5-bound metal contaminants - Zhigang Yu; Zhan Sun; Lanzheng Liu; Chao Li; Xin Zhang; Gzalnur Amat; Mohan Ran; Xiaoyue Hu; Yunxiang Xu; Xiulan Zhao; Jun Zhou (Environmental Pollution, 2024)

A multi-condition denoising diffusion probabilistic model controls the reconstruction of 3D digital rocks - Xin Luo; Jianmeng Sun; Ran Zhang; Peng Chi; Ruikang Cui (Computers & Geosciences, 2024)

Dopant-Enhanced harmonization of α-Fe2O3 oxygen migration and surface catalytic reactions during chemical looping reforming of methane - Hui-Xin Zhang; Xi-Yang Yu; Xue Su; Xin Gao; Zheng-Qing Huang; Bolun Yang; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Ionic liquids bonded in mesoporous HAP serve as efficient catalysts for CO2 fixation - Decun Luo; Zhen-Yu Zhang; Hao Yuan; Xi-Yang Yu; Xin Gao; Zhun Hu; Chun-Ran Chang (Chemical Engineering Journal, 2024)

Na2S-modified biochar for Hg(II) removal from wastewater: A techno-economic assessment - Wenwen Zhao; Zhongsheng Zhang; Yuan Xin; Ran Xiao; Feng Gao; Haitao Wu; Wenfeng Wang; Qiang Guan; Kangle Lu (Fuel, 2024)

Bioremediation of chlorinated ethenes contaminated groundwater and the reactive transport modeling – A review - Moye Luo; Xiaodong Zhang; Xin Zhu; Tao Long; Shaohua Cao; Ran Yu (Environmental Research, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

Targeting mitophagy for neurological disorders treatment: advances in drugs and non-drug approaches - Xiong Yang; Yu Zhang; Jia-xin Luo; Tao Zhu; Zhao Ran; Ben-Rong Mu; Mei-Hong Lu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Wastewater inputs reduce the CO2 uptake by coastal oceans - Yunxiao Li; Liang Xue; Xufeng Yang; Qinsheng Wei; Ming Xin; Ming Xue; Chenhua Han; Ping Han; Xiangyu Liu; Han Zang; Pengjin Yang; Xiangbin Ran; et al. (Science of The Total Environment, 2023)

Precise classification and regional delineation of maturity groups in soybean cultivars across China - Wenwen Song; Luping Liu; Shi Sun; Tingting Wu; Haiyan Zeng; Shiyan Tian; Bincheng Sun; Wenbin Li; Lijun Liu; Shuming Wang; Han Xing; Xin’an Zhou; et al. (European Journal of Agronomy, 2023)

Kilogram-scale synthesis of carbon dots with high-efficiency full-color solid-state fluorescence using an aggregation-induced emission strategy - Hui Ding; Ran Zhao; Zi-Hui Zhang; Jia-Jia Yang; Zheng Wang; Lu-Lan Xiao; Xue-Hua Li; Xin-Jian He; Huan-Ming Xiong (Chemical Engineering Journal, 2023)

Two new constituents from the aerial parts of Salvia miltiorrhiza Bge - Fan Yang; Jia Li; Xin-Lei Du; Shi-Jun Wang; Xiang-Hao Xu; Yong-Qing Zhang; Ran Yang (Natural Product Research, 2023)

Urbanization reduces soil microbial network complexity and stability in the megacity of Shanghai - Lan Liu; Zhaochen Zhang; Xin Wang; Ran Zhang; Meng Wang; Nina Wurzburger; Junxiang Li; Jian Zhang (Science of The Total Environment, 2023)

Ultra-purification of heavy metals and robustness of calcium silicate hydrate (C–S–H) nanocomposites - Qi Liu; Pan Feng; Lijing Shao; Xin Liu; Chen Chen; Jinyuan Lu; Chen Ling; Youfa Zhang; Dewen Sun; Qianping Ran (Chemosphere, 2023)

The effect of chlorogenic acid, a potential botanical insecticide, on gene transcription and protein expression of carboxylesterases in the armyworm (Mythimna separata) - Dong-jiang Lin; Ya-xin Zhang; Yong Fang; San-ji Gao; Ran Wang; Jin-da Wang (Pesticide Biochemistry and Physiology, 2023)

Black phosphorus quantum dots induced ferroptosis in lung cell via increasing lipid peroxidation and iron accumulation - Liangding Dou; Rong Liu; Zhaojizhe Wang; Zhi Huang; Lei Wang; Mo Lin; Xin Hou; Jinwen Zhang; Tantan Cheng; Qi He; Dai Wang; Dongbei Guo; et al. (Food and Chemical Toxicology, 2023)

The spatial coordinates projection method for generating digital geologic cross sections from the multi-source terrain and geologic data - Xingwei Wang; Ran Wang; Yonghui Xin; Haidong Zhang; Xin Han; Wanshan Lei; Gangfeng Wei (Earth Science Informatics, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strategic tillage is a promising alternative to conventional and no-tillage: Evidence from a 12-year field trial in a double-cropped rice system - Xing Wang; Cong He; Bai-Jian Lin; Xin Zhao; Ran Zhang; Ling-Tao Zhong; Xiao-Ping Xiao; Hai-Lin Zhang (European Journal of Agronomy, 2023)

Remotely sensed lake area changes in permafrost regions of the Arctic and the Tibetan Plateau between 1987 and 2017 - Yang Su; Youhua Ran; Guoqing Zhang; Xin Li (Science of The Total Environment, 2023)

Degradation and filling modification of plastic waste for improvement of the slurryability of coal-plastic-water slurry - Junjie Zhai; Renfu Xu; Qihui He; Shenglin Pan; Xin Wang; Ran Zhang; Yahui Feng; Baixing Hu (Fuel, 2023)

Three-dimensional macroporous structure and surface carbon-coating modification of stainless-steel anode boost bioelectrocatalytic performance - Cheng-Yan Liu; Hao-Yi Cheng; Si-Yuan Zhai; Ran Zeng; De-Xin Zhang; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Black phosphorus quantum dots induce autophagy and apoptosis of human bronchial epithelial cells via endoplasmic reticulum stress - Lei Wang; Mo Lin; Xin Hou; Liangding Dou; Zhi Huang; Rong Liu; Jinwen Zhang; Chuchu Cai; Chen Chen; Ying Liu; Dai Wang; Dongbei Guo; et al. (Chemosphere, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Efficient catalytic oxidation of chlorinated volatile organic compounds over RuO2-WOx/Sn0.2Ti0.8O2 catalysts: Insight into the Cl poisoning mechanism of acid sites - Feiyi Zhou; Qi Xin; Yujie Fu; Zhesheng Hua; Yi Dong; Mingchu Ran; Hao Song; Shaojun Liu; Ruiyang Qu; Yang Yang; Xiao Zhang; Chenghang Zheng; et al. (Chemical Engineering Journal, 2023)

CX3CR1 modulates SLE-associated glomerulonephritis and cardiovascular disease in MRL/lpr mice - Xavier Cabana-Puig; Ran Lu; Shuo Geng; Jacquelyn S. Michaelis; Vanessa Oakes; Caitlin Armstrong; James C. Testerman; Xiaofeng Liao; Razan Alajoleen; Michael Appiah; Yao Zhang; Christopher M. Reilly; et al. (Inflammation Research, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

Visualization experiment and flow homogenization optimization of the multi-path plenum chamber system using a perforated plate - Wanqing Zhang; Angui Li; Ran Gao; Xin Gao; Changqing Yang (Building and Environment, 2023)

Fast asteroidal period inversion by parallel acceleration-based three-step reduced voting - Yong-Xiong Zhang; Xiao-Ping Lu; Tan Guo; Xin-Ran Li (Advances in Space Research, 2023)

Inconsistent patterns of Holocene rainfall changes at the East Asian monsoon margin compared to the core monsoon region - Xin Zhou; Tao Zhan; Ning Tan; Luyao Tu; John P. Smol; Shiwei Jiang; Fangming Zeng; Xiaoyan Liu; Xiangzhong Li; Guangxin Liu; Yi Liu; Ran Zhang; et al. (Quaternary Science Reviews, 2023)

Effect of supercritical carbon dioxide on bacterial community, volatile profiles and quality changes during storage of Mongolian cheese - Jing Feng; Yuanrong Zheng; Xin Zhang; Ran Zhou; Ming Ma (Food Control, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Identification of mutational signature for lung adenocarcinoma prognosis and immunotherapy prediction - Sainan Zhang; Mengyue Li; Yilong Tan; Juxuan Zhang; Yixin Liu; Wenbin Jiang; Xin Li; Haitao Qi; Lefan Tang; Ran Ji; Wenyuan Zhao; Yunyan Gu; et al. (Journal of Molecular Medicine, 2022)

Feasibility of Surfgrass Phyllospadix iwatensis Transplantation Along the Rocky Coasts of Shandong Peninsula, China - Jiaxin Zhan; Ran Cheng; Xin Hou; Huan Wang; Peidong Zhang; Bin Kang; Wentao Li (Journal of Ocean University of China, 2022)

Therapeutic effect of the sulforaphane derivative JY4 on ulcerative colitis through the NF-κB-p65 pathway - Xiu-Juan Zhao; Yi-Ran Zhang; Wen-Fei Bai; Tong-Yan Sun; Yu-Fen Yang; Tong-Xin Wang; Cui-Gai Bai (Inflammopharmacology, 2022)

Investigation on long-term progressive deformation of engineering slope based on comprehensive monitoring - Shi-shu Zhang; Song-feng Guo; Sheng-wen Qi; Feng-jiao Tang; Jin-shan Hu; Xiao-ping Zhao; Cong-yan Ran; Xin Wang; Yu Zou; Xiao-lin Huang; Bo-wen Zheng; Ning Liang (Journal of Mountain Science, 2022)

Terrestrial carbon cycle model-data fusion: Progress and challenges - Xin Li; Hanqing Ma; Youhua Ran; Xufeng Wang; Gaofeng Zhu; Feng Liu; Honglin He; Zhen Zhang; Chunlin Huang (Science China Earth Sciences, 2021)

Elabela prevents angiotensin II-induced apoptosis and inflammation in rat aortic adventitial fibroblasts via the activation of FGF21–ACE2 signaling - Juan-Juan Song; Mei Yang; Ying Liu; Jia-Wei Song; Xiao-Yan Liu; Ran Miao; Zhen-Zhou Zhang; Yu Liu; Yi-Fan Fan; Qian Zhang; Ying Dong; Xin-Chun Yang; et al. (Journal of Molecular Histology, 2021)

Marinobacter caseinilyticus sp. nov., Isolated from Saline Soil - Yanfang Nie; Xin Su; Dildar Wu; Ran Zhang; Ruijun Wang; Zhe Zhao; Maripat Xamxidin; Cong Sun; Min Wu (Current Microbiology, 2021)

Estimation of the longitudinal dispersion coefficient using a two-zone model in a channel partially covered with artificial emergent vegetation - Jiao Zhang; Wen-Xin Huai; Hao-Ran Shi; Wei-Jie Wang (Environmental Fluid Mechanics, 2021)

Sustainable strategy for municipal solid waste disposal in Hong Kong: current practices and future perspectives - Ran Jing; Tongzhou Liu; Xin Tian; Hamidreza Rezaei; Chen Yuan; Jin Qian; Zhen Zhang (Environmental Science and Pollution Research, 2020)

Morphological and Anatomical Differences among Three Seagrass Species in a High-energy Coastal Area Typically Dominated by Surfgrass in a Rocky Coastal Area of Shandong Peninsula, China - Wen-Tao Li; Jia Song; Chongfeng Zhong; Xin Hou; Ran Cheng; Pei-dong Zhang (Ocean Science Journal, 2020)

Juxtaposed membranes underpin cellular adhesion and display unilateral cell division of multicellular magnetotactic prokaryotes - Xin‐Xin Qian; Claire‐Lise Santini; Artemis Kosta; Nicolas Menguy; Hugo Le Guenno; Wenyan Zhang; Jinhua Li; Yi‐Ran Chen; Jia Liu; François Alberto; Leon Espinosa; Tian Xiao; et al. (Environmental Microbiology, 2020)
Summary Multicellular magnetotactic prokaryotes (MMPs) exhibit peculiar coordination of swimming along geomagnetic field lines. Approximately 40–80 cells assemble, with a helical geometry or axisymmetry, into spherical or ellipsoidal MMPs respectively. To contribute to a comprehensive understanding of bacterial multicellularity here we took multiple microscopic approaches to study the diversity, assembly, reproduction and motility of ellipsoidal MMPs. Using correlative fluorescence in situ hybridization and scanning electron microscopy analysis, we found an unexpected diversity in populations of ellipsoidal MMPs in the Mediterranean Sea. The high‐pressure freezing/freeze substitution fixation technique allowed us to show, for the first time, that cells adhere via juxtaposed membranes and are held together by a rimming lattice. Fluorescence confocal microscopy and ultrathin section images revealed not only the one‐layer hollow three‐dimensional architecture, but also periphery–core unilateral constriction of constituent cells and unidirectional binary fission of the ellipsoidal MMPs. This finding suggests the evolution toward MMPs multicellularity via the mechanism of incomplete separation of offspring. Remarkably, thousands of flagellar at the periphery surface of cells underpin the coordinated swimming of MMPs in response to mechanical, chemical, magnetic and optical stimuli, including a magnetotactic photokinesis behaviour. Together these results unveil the unique structure and function property of ellipsoidal MMPs.

Correction to: Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Anaerophilus nitritogenes gen. nov., sp. nov., isolated from salt lake sediment in Xinjiang Province, China - Ran Zhang; Yan Zeng; Tian-Qi Wang; Xin-Mei Wang; Yi-Yu Shi; Jia-Tian Zou; Cong Sun; Gui-Shan Zhang; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2020)

Suitable habitat prediction of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) and its implications for conservation in Baihe Nature Reserve, Sichuan, China - Xin Dong; Yuan-meng-ran Chu; Xiaodong Gu; Qiongyu Huang; Jindong Zhang; Wenke Bai (Environmental Science and Pollution Research, 2019)

Description of Wenzhouxiangella salilacus sp. nov., a moderate halophilic bacterium isolated from a salt lake in Xinjiang Province, China - Shuai-Bo Han; Xin-Jun Hou; Yang-Huan Yu; Zhao Ju; Ran Zhang; Rui-Jun Wang; Yang-Hui Ye; Yan-Hu Ren; Wei-Yan Zhang; Min Wu (Antonie van Leeuwenhoek, 2019)

A Case of Chromoblastomycosis Caused by Fonsecaea Pedrosoi and Investigation of the Pathogenic Fungi - Ruifeng Zhang; Yuping Ran; Hao Zhang; Yaling Dai; Xin Ran; Chaoliang Zhang; Wei Qin; Liyan Xi (Mycopathologia, 2019)

Novel technologies applied for recovery and value addition of high value compounds from plant byproducts: A review - Xin-li Ran; Min Zhang; Yuchuan Wang; Benu Adhikari (Critical Reviews in Food Science and Nutrition, 2019)

A novel missense mutation of $$ADAR1$$ ADAR 1 gene in a Chinese family leading to dyschromatosis symmetrica hereditaria and literature review - Shuai-Mei Liu; Meng-Xia Ni; Ming-Chao Zhang; Pei-Ran Zhu; Qiu-Yu Wu; Wei-Jun Jiang; Jing Zhang; Wei-Wei Li; Xin-Yi Xia (Journal of Genetics, 2017)

QSAR modeling and in silico design of small-molecule inhibitors targeting the interaction between E3 ligase VHL and HIF-1 $$α $$ α - Jing Pan; Yanmin Zhang; Ting Ran; Anyang Xu; Xin Qiao; Lingfeng Yin; Weineng Zhou; Lu Zhu; Junnan Zhao; Tao Lu; Yadong Chen; Yulei Jiang (Molecular Diversity, 2017)

A naturally occurring conditional albino mutant in rice caused by defects in the plastid-localized OsABCI8 transporter - Xiuyu Zeng; Ran Tang; Herong Guo; Shanwen Ke; Bin Teng; Yu-Hung Hung; Zhenjiang Xu; Xin-Ming Xie; Tzung-Fu Hsieh; Xiang-Qian Zhang (Plant Molecular Biology, 2017)

miR-143 regulates proliferation and differentiation of bovine skeletal muscle satellite cells by targeting IGFBP5 - Wei Ran Zhang; Hui Na Zhang; Yi Min Wang; Yang Dai; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2017)

Global mapping of artificial surfaces at 30-m resolution - XueHong Chen; Xin Cao; AnPing Liao; LiJun Chen; Shu Peng; Miao Lu; Jin Chen; WeiWei Zhang; HongWei Zhang; Gang Han; Hao Wu; Ran Li (Science China Earth Sciences, 2016)

Slow-release nitrogen fertilizers can improve yield and reduce Cd concentration in pakchoi (Brassica chinensis L.) grown in Cd-contaminated soil - Ran-Ran Zhang; Yue Liu; Wan-Lei Xue; Rong-Xin Chen; Shao-Ting Du; Chong-Wei Jin (Environmental Science and Pollution Research, 2016)

Complete genome sequence and comparative genome analysis of a new special Yersinia enterocolitica - Guoxiang Shi; Mingming Su; Junrong Liang; Ran Duan; Wenpeng Gu; Yuchun Xiao; Zhewen Zhang; Haiyan Qiu; Zheng Zhang; Yi Li; Xiaohe Zhang; Yunchao Ling; et al. (Archives of Microbiology, 2016)

Strengthened African summer monsoon in the mid-Piacenzian - Ran Zhang; Zhongshi Zhang; Dabang Jiang; Qing Yan; Xin Zhou; Zhigang Cheng (Advances in Atmospheric Sciences, 2016)

Exendin-4 Enhances Motor Function Recovery via Promotion of Autophagy and Inhibition of Neuronal Apoptosis After Spinal Cord Injury in Rats - Hao-Tian Li; Xing-Zhang Zhao; Xin-Ran Zhang; Gang Li; Zhi-Qiang Jia; Ping Sun; Ji-Quan Wang; Zhong-Kai Fan; Gang Lv (Molecular Neurobiology, 2016)

Methane and nitrous oxide emissions under no‐till farming in China: a meta‐analysis - Xin Zhao; Sheng‐Li Liu; Chao Pu; Xiang‐Qian Zhang; Jian‐Fu Xue; Ran Zhang; Yu‐Qiao Wang; Rattan Lal; Hai‐Lin Zhang; Fu Chen (Global Change Biology, 2016)
No‐till ( NT ) practices are among promising options toward adaptation and mitigation of climate change. However, the mitigation effectiveness of NT depends not only on its carbon sequestration potential but also on soil‐derived CH 4 and N 2 O emissions. A meta‐analysis was conducted, using a dataset involving 136 comparisons from 39 studies in China, to identify site‐specific factors which influence CH 4 emission, CH 4 uptake, and N 2 O emission under NT . Comparative treatments involved NT without residue retention ( NT 0), NT with residue retention ( NTR ), compared to plow tillage ( PT ) with residue removed ( PT 0). Overall, NT 0 significantly decreased CH 4 emission by ~30% ( P 0.05) compared to PT 0 with an average emission 218.8 kg ha −1 for rice paddies. However, the increase in N 2 O emission could partly offset the benefits of the decrease in CH 4 emission under NT compared to PT 0. NTR significantly enhanced N 2 O emission by 82.1%, 25.5%, and 20.8% ( P 0.05) compared to PT 0 for rice paddies, acid soils, and the first 5 years of the experiments, respectively. The results from categorical meta‐analysis indicated that the higher N 2 O emission could be mitigated by adopting NT within alkaline soils, for long‐term duration, and with less N fertilization input when compared to PT 0. In addition, the natural log (lnR) of response ratio of CH 4 and N 2 O emissions under NT correlated positively (enhancing emission) with climate factors (temperature and precipitation) and negatively (reducing emission) with experimental duration, suggesting that avoiding excess soil wetness and using NT for a long term could enhance the benefits of NT . Therefore, a thorough understanding of the conditions favoring greenhouse gas(es) reductions is essential to achieving climate change mitigation and advancing food security in China.

microRNA-128 regulates the proliferation and differentiation of bovine skeletal muscle satellite cells by repressing Sp1 - Yang Dai; Wei Ran Zhang; Yi Min Wang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (Molecular and Cellular Biochemistry, 2016)

MAPK cascade‐mediated regulation of pathogenicity, conidiation and tolerance to abiotic stresses in the entomopathogenic fungus M etarhizium robertsii - Xiaoxuan Chen; Chuan Xu; Ying Qian; Ran Liu; Qiangqiang Zhang; Guohong Zeng; Xin Zhang; Hong Zhao; Weiguo Fang (Environmental Microbiology, 2016)
Summary M etarhizium robertsii has been used as a model to study fungal pathogenesis in insects, and its pathogenicity has many parallels with plant and mammal pathogenic fungi. MAPK (Mitogen‐activated protein kinase) cascades play pivotal roles in cellular regulation in fungi, but their functions have not been characterized in M . robertsii . In this study, we identified the full complement of MAPK cascade components in M . robertsii and dissected their regulatory roles in pathogenesis, conidiation and stress tolerance. The nine components of the Fus3, Hog1 and Slt2‐ MAPK cascades are all involved in conidiation. The Fus3‐ and Hog1‐ MAPK cascades are necessary for tolerance to hyperosmotic stress, and the Slt2‐ and Fus3‐ MAPK cascades both mediate cell wall integrity. The Hog1 and Slt2‐ MAPK cascades contribute to pathogenicity; the Fus3‐ MAPK cascade is indispensable for fungal pathogenesis. During its life cycle, M . robertsii experiences multiple microenvironments as it transverses the cuticle into the haemocoel. RNA ‐seq analysis revealed that MAPK cascades collectively play a major role in regulating the adaptation of M . robertsii to the microenvironmental change from the cuticle to the haemolymph. The three MAPKs each regulate their own distinctive subset of genes during penetration of the cuticle and haemocoel colonization, but they function redundantly to regulate adaptation to microenvironmental change.

Paenibacillus chinensis sp. nov., isolated from maize (Zea mays L.) seeds - Yang Liu; Ran Zhao; Ronghuan Wang; Su Yao; Lei Zhai; Xin Zhang; Chuanyong Chen; Yanhua Cao; Tianjun Xu; Yuanyuan Ge; Jiuran Zhao; Chi Cheng (Antonie van Leeuwenhoek, 2016)

The role of microRNA-1 and microRNA-206 in the proliferation and differentiation of bovine skeletal muscle satellite cells - Yang Dai; Yi Min Wang; Wei Ran Zhang; Xin Feng Liu; Xin Li; Xiang Bin Ding; Hong Guo (In Vitro Cellular & Developmental Biology - Animal, 2016)

Fragment virtual screening based on Bayesian categorization for discovering novel VEGFR-2 scaffolds - Yanmin Zhang; Yu Jiao; Xiao Xiong; Haichun Liu; Ting Ran; Jinxing Xu; Shuai Lu; Anyang Xu; Jing Pan; Xin Qiao; Zhihao Shi; Tao Lu; et al. (Molecular Diversity, 2015)

Earthworms modify microbial community structure and accelerate maize stover decomposition during vermicomposting - Yuxiang Chen; Yufen Zhang; Quanguo Zhang; Lixin Xu; Ran Li; Xiaopei Luo; Xin Zhang; Jin Tong (Environmental Science and Pollution Research, 2015)

Erratum to: Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Kerui Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2015)

Identification of a Novel Mutation in the Presenilin 1 Gene in a Chinese Alzheimer’s Disease Family - Bo Deng; Yan Lian; Xin Wang; Fan Zeng; Bin Jiao; Ye-Ran Wang; Chun-Rong Liang; Yu-Hui Liu; Xian-Le Bu; Xiu-Qing Yao; Chi Zhu; Lu Shen; et al. (Neurotoxicity Research, 2014)

The Pseudomonas aeruginosa Mannose Sensitive Hamemagglutination Strain (PA-MSHA) Induces a Th1-Polarizing Phenotype by Promoting Human Dendritic Cells Maturation - Yunyan Zhang; Hongtao Wang; Youqiang Li; Ke Chen; Jinmei Ye; Xin Liao; Yiyang Chen; Wei Ran (Indian Journal of Microbiology, 2014)

Cloning and in silico analysis of a cinnamyl alcohol dehydrogenase gene in Pennisetum purpureum - RAN TANG; XIANG-QIAN ZHANG; YOU-HAN LI; XIN-MING XIE (Journal of Genetics, 2014)

Single primary fetal lung cells generate alveolar structures in vitro - Shengliang Zhang; Xin Zhou; Tie Chen; Yanna Shang; Ran Lu; Dongqin Yin; Jin Liu; Hong Xu; Xianming Mo (In Vitro Cellular & Developmental Biology - Animal, 2014)

Lipopolysaccharides Reduce Adipogenesis in 3T3-L1 Adipocytes Through Activation of NF-κB Pathway and Downregulation of AMPK Expression - Lifeng Wang; Linlin Li; Xinjian Ran; Mei Long; Minfang Zhang; Yicun Tao; Xin Luo; Ye Wang; Yi Jiao; Xinmin Mao; Jun Ren (Cardiovascular Toxicology, 2013)

The Antitumor Effect of a New Docetaxel-Loaded Microbubble Combined with Low-Frequency Ultrasound In Vitro: Preparation and Parameter Analysis - Shu-Ting Ren; Yi-Ran Liao; Xiao-Ning Kang; Yi-Ping Li; Hui Zhang; Hong Ai; Qiang Sun; Jing Jing; Xing-Hua Zhao; Li-Fang Tan; Xin-Liang Shen; Bing Wang (Pharmaceutical Research, 2013)

Splice variants DNMT3B4 and DNMT3B7 overexpression inhibit cell proliferation in 293A cell line - Guo Shao; Ran Zhang; Shu Zhang; Shuyuan Jiang; You Liu; Wei Zhang; Yanbo Zhang; Jinping Li; Keri Gong; Xin-Rong Hu; Shi-Wen Jiang (In Vitro Cellular & Developmental Biology - Animal, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Functional recombinant human anti-HBV antibody expressed in milk of transgenic mice - Ran Zhang; Dan Cui; Hong Wang; Chuan Li; Xin Yao; Yaofeng Zhao; Mifang Liang; Ning Li (Transgenic Research, 2012)

Sucrose monolaurate synthesis with Protex 6L immobilized on electrospun TiO2 nanofiber - Xin-Ran Wang; Song-Ping Zhang; Ping Wang (Biotechnology Letters, 2011)

An easy-to-use site-directed mutagenesis method with a designed restriction site for convenient and reliable mutant screening - Bao-zhong Zhang; Xin Zhang; Xiao-ping An; Duo-liang Ran; Yu-sen Zhou; Jun Lu; Yi-gang Tong (Journal of Zhejiang University-SCIENCE B, 2009)

Evaluation of water quality in Er-longshan reservoir by fuzzy model - Ying Zhang; Chun-Hui Fan; Zhuo Diao; Xin-Ran Peng; Xin Bai (Interdisciplinary Sciences: Computational Life Sciences, 2009)

The Prevalence of Type 2 Diabetes and Hypertension in Uygur and Kazak Populations - Yicun Tao; Xinmin Mao; Zijing Xie; Xinjian Ran; Xiaoyan Liu; Ye Wang; Xin Luo; Mengying Hu; Wenning Gen; Minfang Zhang; Tao Wang; Jun Ren; et al. (Cardiovascular Toxicology, 2008)

Role of DNA in Bacterial Aggregation - Hui-Hui Liu; Yi-Ran Yang; Xin-Cheng Shen; Zhi-Ling Zhang; Ping Shen; Zhi-Xiong Xie (Current Microbiology, 2008)

Analysis of Prevalence and Risk Factors of Hypertension Among Uygur Adults in Tushala and Hetian Xinjiang Uygur Autonomous Region - Lin-Lin Li; Xiao-Yan Liu; Jian-Xin Ran; Ye Wang; Xin Luo; Tao Wang; Jun Ren; Mayinuer Aisha; Rebiya Abudureheman; Adalaiti Xiawudong; Xiao-Chun Zhang; Xin-Min Mao (Cardiovascular Toxicology, 2008)